Christianity as a Trauma-Analogous Phenomenon: Nietzsche’s Critique and Therapeutic Ideas in Dawn - Kiesel, Dagmar (Nietzsche on the Art of Living. New Studies from the German-Speaking Nietzsche Research, 2023)
In this article I intend to show that according to Nietzsche’s analyses in Dawn and against the background of modern theories of trauma Christianity may be understood as a trauma-analogous phenomenon. The focus is on the radical invalidation of elementary, natural human needs and the abysmal human depravity and dependence on the divine claimed by the Augustinian doctrine of original sin. Finally, I will critically reflect on Nietzsche's suggestions on the therapy of the psychological trauma caused by Christian socialization.</stron